The evolution and ontogeny of play: comparative perspectives - Gordon Burgardt; Elisabetta Palagi (International Journal of Play, 2023)
This special issue of the International Journal of Play is devoted to the evolution and ontogeny of play and includes papers on various animals, children, and a diversity of phenomena all related to this theme. Papers in the issue provide original data on these species: rheas, Beluga whales, wolves, Japanese monkeys, gorillas, and human children as well as a phylogenetic analysis of social play in primates. While social play is emphasized, object play is also discussed, including in relation to Autism Spectrum Disorder in humans. Theoretical issues are also covered, such as the origins and evolution of object play and its role in social and cultural evolution. Together these papers highlight the myriad aspects of play that need to be integrated into our understanding of a topic now decisively liberated from being viewed primarily from an anthropocentric perspective isolated from its deep biological and evolutionary roots.